Augmented reality in language learning: a systematic literature review of the state-of-the-art and task design considerations - Christou, Eirini; Vassiliou, Paraskevi; Parmaxi, Antigoni (My University, 2025)
Augmented Reality (AR) allows users to experience a digital world that blends seamlessly with the physical world, creating an immersive and interactive experience. This study presents a review of the recent literature pertaining to AR in language learning for the last five years (2019-2023). This work consists of the review of 48 articles and follows the PRISMA framework for systematic reviews, focusing on devices and software used, level of education being employed, language focus, theoretical framework considerations as well as task design and classroom orchestration practices. The article focuses on presenting a typology of three AR-mediated task designs (information transmission activities, social constructivist activities and constructivist/ionist activities) and six different types of AR-mediated tasks (translating or visualising information, completing quests or missions, collaborating in location-based exploration game/ mystery, communicating with a virtual avatar, facilitating segmental production and creating AR artifacts). The article illustrates the decisions instructors make prior to implementing AR tasks, and it outlines recommendations and considerations for language instructors to consider when designing and implementing AR tasks for language learning.
Keywords: Augmented reality; language learning; task design; task-based learning; systematic literature review